The T-cell receptor in primates: Identifying and sequencing new owl monkey TRBV gene sub-groups (2005)
The New World primate Aotus nancymaae (owl monkey) has been shown to be an excellent experimental model when studying malarial parasites. Characterising the T-cell receptor (TR) ?? repertoire by means of the different variable beta (TRBV) genes displayed contributes to a better understanding of these lymphocytes’ role in the response against several malarial antigens. This study describes identifying and characterising eleven new TRBV gene sub-groups in cDNA from Aotus nancymaae’s peripheral blood lymphocytes; these 11 gene sequences displayed homology to the previously reported human TRBV3, TRBV10, TRBV11, TRBV14, TRBV18, TRBV19, TRBV20, TRBV25, TRBV27, TRBV29 and TRBV30 sub-groups, resulting in 83% overall homology at the amino acid level. An additional Aotus sequence was found having similarity with the human TRBJ-2–7*01 gene. Evolutionary relationships amongst these sequences and the homologous genes from both New and Old World primates have shown that the TRBV repertoire has been maintained in the species being studied, displaying varying association patterns and substitution rates, depending on the sub-group being studied. The degree of identity observed when comparing human and Aotus genes suggests that these species might have a similar TRBV repertoire.